Powerful curved piezoelectric generator for wearable applications - Jung, Woo-Suk; Lee, Min-Jae; Kang, Min-Gyu; Moon, Hi Gyu; Yoon, Seok-Jin; Baek, Seung-Hyub; Kang, Chong-Yun (ELSEVIER SCIENCE BV, 2015)
With the widespread use of wearable electronics, the flexible piezoelectric energy harvesting devices have been extensively studied to efficiently convert the physical motion of the human body into electrical energy. The major obstacles for realizing a flexible piezoelectric generator include the insufficient output power generation and the poor efficiency at the low-frequency regime. Here, we demonstrate a curved piezoelectric generator favorable for wearable applications, generating a high output power. The curved structure plays a key role to improve the power generation, by effectively distributing the applied force across the piezoelectric layer, as well as to allow operation at the low frequency vibration range. Accordingly, this generator produces similar to 120 V of peak output voltage and 700 I.LA of peak output current during a cycle. Furthermore, our generator can operate at low frequencies below 50 Hz, generating 55 V of output voltage and 2501 A of output current at 35 Hz, and it even works at frequencies as low as 1 Hz. With this generator, we successfully lit up 476 commercial LED bulbs. In addition, we experimentally demonstrate the possibility that the generator can be used in shoes, watches, and clothes as a power source. Our results will provide a framework to enhance the output power of conventional piezoelectric generators, and open a new avenue for realization of self-powered systems, such as wearable electronic devices. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: NANOGENERATOR; EXPLOSION; FILM